2011
DOI: 10.4260/bjft2011140200017
|View full text |Cite
|
Sign up to set email alerts
|

Lactose conversion and the synthesis of galactooligosaccharides in a simultaneous lagged bioprocess using β-galactosidases and probiotic microorganisms

Abstract: SummaryLactose conversion and the production of galactooligosaccharides (GOS) were evaluated in a simultaneous bioprocess using probiotic microorganisms and the addition of β-galactosidases, lagged or otherwise. The fermentation was carried out using normal yogurt cultures, Streptococcus thermophilus and Lactobacillus bulgaricus, associated with two probiotic microorganisms, Bifidobacterium animalis and Lactobacillus acidophilus. An enzymatic preparation containing β-galactosidases of distinct origins, obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Scarce and variable information on GOS synthesis during reduced‐lactose yogurt manufacture employing the enzymatic process is reported. The most recent work has been carried out by Martins et al They reported GOS values between 0.9 and 4.9 g L −1 for fresh hydrolyzed yogurts. On the other hand, some studies reported GOS synthesis in the preparation of traditional yogurts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarce and variable information on GOS synthesis during reduced‐lactose yogurt manufacture employing the enzymatic process is reported. The most recent work has been carried out by Martins et al They reported GOS values between 0.9 and 4.9 g L −1 for fresh hydrolyzed yogurts. On the other hand, some studies reported GOS synthesis in the preparation of traditional yogurts.…”
Section: Resultsmentioning
confidence: 99%
“…and Table (b). Martins et al employed an approach similar to that used in this work (simultaneous enzymatic hydrolysis and fermentation) and the addition of enzyme before the start of fermentation. The lactose values obtained ranged from 0.2 to 68.1 g L −1 for hydrolyzed yogurts depending on the β ‐galactosidase dose, the initial lactose concentration in the milk and the time of enzyme addition.…”
Section: Resultsmentioning
confidence: 99%
“…In the conventional process, enzymatic catalysis first occurs in a substrate at pH between 6.5 and 6.8 and temperatures between 4 and 6º C, for the purpose of minimizing microbiological contamination. This temperature takes the contact time to at least 30 h. In this conventional process, the substrate with low lactose content passes to the second stage of processing when the industrial application of lactic culture and early fermentation take place (MARTINS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the production medium using S. salmonicolor (Valduga et al, 2009(Valduga et al, , 2014 and for S. pararoseus (Cabral et al, 2011). This methodology is also applied to obtain other bioproducts, such as biomass (Santos et al, 2012), galacto-oligosaccharides (Lisboa et al, 2012a;Lisboa et al, 2012b), dairy drinks (Martins et al, 2011;Martins et al, 2012;Burkert et al, 2012), enzymes (Maldonado et al, 2012;Campello et al, 2012;Alves et al, 2010), synthesis of natural flavors (Anschau et al, 2011;Aragão et al, 2011), phycocyanin (Moraes et al, 2010) and rhamnolipids (Rosa et al, 2010).…”
mentioning
confidence: 99%